A deeper view of the CoRoT-9 planetary system: A small non-zero eccentricity for CoRoT-9b likely generated by planet-planet scattering - Bonomo, A. S.; Hébrard, G.; Raymond, S. N.; Bouchy, F.; Lecavelier Des Etangs, A.; Bordé, P.; Aigrain, S.; Almenara, J. M.; Alonso, R.; Cabrera, J.; Csizmadia, Sz.; Damiani, C.; et al. (EDP Sciences, 2017)
CoRoT-9b is one of the rare long-period (P = 95.3 days) transiting giant planets with a measured mass known to date. We present a new analysis of the CoRoT-9 system based on five years of radial-velocity (RV) monitoring with HARPS and three new space-based transits observed with CoRoT and Spitzer. Combining our new data with already published measurements we redetermine the CoRoT-9 system parameters and find good agreement with the published values. We uncover a higher significance for the small but non-zero eccentricity of CoRoT-9b () and find no evidence for additional planets in the system. We use simulations of planet-planet scattering to show that the eccentricity of CoRoT-9b may have been generated by an instability in which a ∼ 50 M⊕ planet was ejected from the system. This scattering would not have produced a spin-orbit misalignment, so we predict that the CoRoT-9b orbit should lie within a few degrees of the initial plane of the protoplanetary disk. As a consequence, any significant stellar obliquity would indicate that the disk was primordially tilted.
Keywords: Planetary systems; Stars: Individual: CoRoT-9; Techniques: Photometric; Techniques: Radial velocities